Building Spatial Regression Model to Know The influence of Road’s Access & Education to Population Growth of Germany in 2018 - Tuti Purwaningsih; Aliffian Wahyu Raharjo (International Journal of Applied Business and Information Systems, 2020)
Population growth are one of the core information of a nation to make a decision of economics strategy in the future. This study aims to see what infrastructure or education factors affect population growth in Germany using Spatial Regression method through SAR model. Creation of spatial regression model using GeoDa software. The results of this study indicate that education and road infrastructure has a significant effect on population growth in Germany in 2018, the result of modelling proccess can be explained as the following equation: Population = 482443 + (-0.10695 ((11,293) (Education) + (113,8) (Road))) with R2=99,6%.